THE ROLE OF GOVERNMENT IN IMPROVING EDUCATIONAL FACILITIES - Islombek, Karimov (Magister Administrasi Publik Program Pascasarjana Universitas Ngurah Rai, 2025)
Education is the cornerstone of any thriving society, and its quality directly impacts a nation's economic, social, and cultural growth. As such, the government plays a pivotal role in shaping and improving educational facilities, ensuring that all citizens have access to quality education. The role of the government in enhancing educational infrastructure can be explored from various angles, including policy-making, funding, governance, and the development of physical and technological resources. This article examines how governments can improve educational facilities and why their involvement is crucial to fostering an equitable and dynamic educational system. Education plays a crucial role in shaping a nation’s future, and the government is central in ensuring that all citizens have access to quality education. One of the main ways this is achieved is through the establishment and maintenance of educational facilities. In this article, we’ll explore the various roles the government plays in the development, funding, and management of educational infrastructure.